Post-Quantum Cryptography in Automotive Scenarios (V2X and V2V) - Mariana do Carmo Barata Gonçalves; Valderi Leithardt (2026)
Gonçalves, Mariana ; Reis Quietinho Leithardt, Valderi (2026), “Post-Quantum Cryptography in Automotive Scenarios (V2X and V2V)”, Mendeley Data, V1, doi: 10.17632/czx6vk5hsr.1